Utilizing the potential of the Tebo River through innovative cendol squid processing - Muhammad Yasir Rizqi Mubarok; Shalsabilla Novarizka; Nuril Hidayah; Yulinda Azzahra; Abdi Alif Rahman; Indri Safitri; Sintia Dona; Selly Oktaviana; Ade Nurfatiah; Hatika Risti; Romadon Romadon (Community Empowerment, 2023)
Lubuk Besar Village, especially the Tebo River, has abundant marine products, one of which is squid. However, the squid catch is sold directly to collectors. This is a problem because there is no innovation so it has not had an impact on improving the economy. The aim of this community service is to increase innovation in processing squid into squid sauce which will have an impact on wider marketing. The program method is in the form of counseling and assistance in the production and packaging processes for the Sungai Tebo MSME group, totaling 15 people. This program produces a new processed seafood product in the form of cendol squid with the name 'Samibo' which has been packaged in a good manner and is fit for distribution.